Population Genomic Analyses Confirm Male-Biased Mutation Rates in Snakes. (27th January 2021) - Schield, Drew R; Perry, Blair W; Nikolakis, Zachary L; Mackessy, Stephen P; Castoe, Todd A
Abstract: Male-biased mutation rates occur in a diverse array of organisms. The ratio of male-to-female mutation rate may have major ramifications for evolution across the genome, and for sex-linked genes in particular. In ZW species, the Z chromosome is carried by males two-thirds of the time, leading to the prediction that male-biased mutation rates will have a disproportionate effect on the evolution of Z-linked genes relative to autosomes and the W chromosome. Colubroid snakes (including colubrids, elapids, and viperids) have ZW sex determination, yet male-biased mutation rates have not been well studied in this group. Here we analyze a population genomic dataset from rattlesnakes to quantify genetic variation within and genetic divergence between species. We use a new method for unbiased estimation of population genetic summary statistics to compare variation between the Z chromosome and autosomes and to calculate net nucleotide differentiation between species. We find evidence for a 2.03-fold greater mutation rate in male rattlesnakes relative to females, corresponding to an average μ Z / μ A ratio of 1.1. Our results from snakes are quantitatively similar to birds, suggesting that male-biased mutation rates may be a common feature across vertebrate lineages with ZW sex determination.